Case Report: Two episodes of hyperinflammation in an infant consistent with multisystem inflammatory syndrome in children: recurrence or rather two different diseases? - Dechant, Markus-Johann; Michel, Holger; Kabesch, Michael; Melter, Michael; Gerling, Stephan (Frontiers in Pediatrics, 2025)
Multisystem inflammatory syndrome in children (MIS-C) is a hyperinflammatory disease that occurs after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report a 9-month-old male infant with two episodes of hyperinflammatory disease, each involving the coronary arteries, within a short period of time during the SARS-CoV-2 pandemic. Although both episodes met the official criteria for MIS-C, this case illustrates the difficulty in distinguishing MIS-C from its main differential diagnosis, Kawasaki disease (KD). Recurrence of postviral hyperinflammatory disease is rare. Compared with KD, the recurrence of MIS-C is even rarer, but clinicians should be aware of this possibility. Our case also emphasizes the need to follow up these patients closely and to detect sequelae regularly, especially cardiovascular sequelae, at an early stage.